Research into milk homogenization in the pulsation machine with a vibrating rotor - Samoichuk, Kyrylo; Kiurchev, Sergey; Oleksiienko, Vadym; Palyanichka, Nadiya; Verholantseva, Valentina (Eastern-European Journal of Enterprise Technologies, 2016)
In the modern dairy production schemes one of the main problems is high energy consumption in the process of homogenization. One of the perspective ways to solve this problem is to research and develop the variety of rotor-pulsation machine – pulsation machine with a vibrating rotor. Homogenization in such machine allows getting high values of emulsion flow acceleration and using the resonance phenomenon that has a positive impact on quality and energy consumption of the machine. As a result of analytical researches, the hypothesis is suggested about the key role of emulsion acceleration in the process of milk emulsion fat phase dispersing in the pulsation machine with a vibrating rotor. We received dependences that associate instantaneous and average acceleration of the emulsion with the frequencies of rotation and vibration of the rotor, its diameter and amount of openings. These dependences allow determining conditions for increasing degree of emulsion dispersing. The experimental researches resulted in defining interconnection between acceleration of emulsion and dispersion of fat phase of milk, which confirms the hypothesis about the mechanism of homogenization in the pulsation machine with a vibrating rotor. The middle sizes of fat globules of milk are found to be dependent on the frequency of rotation and amplitude of rotor vibration. With the frequencies of rotation of the crank shaft up to 2880 rpm and amplitude of rotor oscillation 1 mm it is possible to get milk emulsion with the average size of around 0.8 μm. The results of the research prove the use of such machines in the technological processing lines of milk to be promising. The investigated machine allows receiving highly dispersed emulsion that is on the same level as processed in valve homogenizers with considerable decrease in energy consumption.